How data inspection and consideration, provides for index compression and record access optimization of genetic databases. - Zirkind, Givon (Software engineering notes.)
With the many advances in computer hardware, the constant and historical challenges of optimization in processing and data storage diminished if not disappeared almost entirely. With hard drives getting larger and larger, while prices keep dropping; and the same occurring to memory; computer programs have turned more and more into bloatware. Likewise, processing speed has made efficiency and streamlining of program code, virtually a non-issue. The field of genetic research provides the perfect regeneration of those classical challenges to computer engineers. Genetic research requires extremely large databases, with extremely large indexes, with complex search criteria, with an extremely large number of inquiries and searches initiated remotely. Often, search requests are initiated over long geographic distances. To improve database performance, indexing access speed, and reduce index size, the author developed a new, genetic database, herein discussed.